A-03 SCAT5 Cognitive Screening Normative Data and Reliable Change Indices. (18th June 2020) - Bailey, C; Meyer, J; Tangen, C; Deane, R; Briskin, S; Gunstad, J; Fastenau, P; Smith, P; Solomon, M; Kelly, A W
Abstract: Objective: This study provides normative data on the SCAT5 Cognitive Screening, establishes test-retest reliability, and creates clinically relevant cut points for low performance. Method: The multisport baseline sample was composed of 727 uninjured college athletes (52% female) at a Division I university who were administered the SCAT5 before the 2017–2018 season. Descriptive statistics, including base rates of low performance, were calculated for SCAT5 indices. Repeat baseline testing was completed by 325 athletes (48% female) at 1 year (days M = 352.56;SD = 56.03) who were included in the test-retest reliability and practice effect analyses. Reliable change indices were calculated. Results: Descriptive statistics for SCAT5 were computed for both baselines (Baseline 1: SAC total M = 35.15, SD = 4.93; immediate recall total M = 20.01, SD = 3.46; delayed recall total M = 6.43, SD = 1.75). A difference in descriptive statistics and practice effects by sex on the SCAT5 Cognitive Screening has been demonstrated (Bailey, Meyer, Tangen et al., under review). For female athletes, the 1st administration cutoff scores for abnormal performance (<10th%ile) included SAC total score = 33, immediate recall score = 18, and delayed recall score = 6. For male athletes, the 1st administration cutoff scores for abnormal performance (<10th%ile) included SAC total score = 30, immediate recall score = 17, and delayed recall score = 5. Test-retest reliability of the SAC was similar to previous versions but varied by sex. Reliable change indices (RCI) were created with cut points for significant change. Conclusions: The present study provides clinically relevant normative data for the SCAT5 Cognitive Screening. Cut points for low performance on both reliable chance indices (RCIs) and normative performance reflected meaningful sex differences that could influence clinical interpretation.